SMEs THE WAY FORWARD FOR UNIVERSITY-INDUSTRY ENGAGEMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 June 2015 – Malaysian universities should look to the small medium industries (SME) sector to enhance universityindustry engagement. This was emphasised by panelists of the inaugural CEO Forum titled “Role of Industry in Strengthening the University of the 21 century” organised by Universiti Sains Malaysia’s Division of Industry and Community Network (BJIM).